2024
DOI: 10.3390/su16083269
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning Delivery Methods for a Sustainable Learning Environment: A Delphi Study

Ali Saleh Alammary

Abstract: The outbreak of COVID-19 necessitated social distancing. Universities around the world were left with two options: a total suspension or a major reduction in students’ attendance. While the nature of many courses made it very difficult to teach them online, blended learning was the most suitable approach to teach these types of courses. Academics and educational institutions have realized the significance of blended learning not only as a response to immediate disruptions but also as a pivotal element in foste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…The authors of the publication [39] suggest that social media can be a very effective tool for building a course community, especially in terms of exchanging official and unofficial information between students. The research conducted by them confirms that the proper use of social media could promote a new era of social learning, social presence, and an alternative platform to foster online learning [37]. One interesting tool to support social learning is the Perusall platform [40].…”
Section: Pandemic Experiments and Experiencesmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors of the publication [39] suggest that social media can be a very effective tool for building a course community, especially in terms of exchanging official and unofficial information between students. The research conducted by them confirms that the proper use of social media could promote a new era of social learning, social presence, and an alternative platform to foster online learning [37]. One interesting tool to support social learning is the Perusall platform [40].…”
Section: Pandemic Experiments and Experiencesmentioning
confidence: 95%
“…For example, they suggest preparing short, high-definition video tutorials as part of the pre-class activity to match the current way young people perceive knowledge. Video and multimedia are important tools for didactic work in the BL formula, especially FC [37]. One of them is the webinar analyzed by Kumar et al [38].…”
Section: Pandemic Experiments and Experiencesmentioning
confidence: 99%
“…A growing body of research indicates that blended learning can foster sustainable students' engagement and success. By combining face-to-face and online components, students can access knowledge from various sources, thereby improving their learning outcomes [19,20]. Dziuban, Graham, Moskal, Norberg and Sicilia [1] observed that the diverse activities in blended courses positively motivate students and can boost class attendance.…”
Section: Research Backgroundmentioning
confidence: 99%